As sociedades pré-coloniais na fronteira Brasil Uruguai: um olhar para além do colonizador europeu - Rosa, Carlos Roberto de Castilho (2020)
This dissertation aims thinking on precolonial societies that lived border Santana do Livramento (Brazil) and Rivera (Uruguay) focusing artefacts from material culture selected and displayed at Museu do Patrimonial Regional de Rivera in Uruguay using the heritage education methodology articulated to history teaching, trying to enable students from basic education, fundamental teaching to approach local early human societies and envolve these students to build an understanding on these past societies as historical and their agents as historical subject.The research is qualitative and bibliography based on bibliography review in the field of knowledge to verify the research question. As result, we can say that local early human societies developed techniques to make their tools and used them to different purposes. Another result is related to the research question of this study and the students realized the ancient societies as historical. In conclusion we can say that local past societies made their tools, lithic and ceramic artefacts, but we realized that early local human socities experienced different cultural stages, thus, the farther the artefacts were made more rudimentary they were,however these artefacts supplied the expectation of survival from these ancient human societies.